MAXIMIZING USABILITY OF IIUM GIGEASE: A SHORT-TERM EMPLOYMENT PLATFORM FOR IIUM STUDENTS AND NEIGHBOURING COMMUNITIES - MOHAMAD YUSRI, MOHD KHAIRI; SHEIKH ABDUL AZIZ, MADIHAH (Journal of Information Systems and Digital Technologies, 2024)
Due to the rising cost of living in Malaysia, students—who typically have no source of income—are increasingly facing financial challenges. These challenges often compel them to make sacrifices in essential areas, such as nutrition, in order to survive throughout their study period. In response, the IIUM GIGEASE mobile application was developed as a platform to provide temporary job opportunities for students and the neighbouring communities around IIUM. The project followed the interaction design lifecycle model, which includes stages such as establishing requirements, designing alternatives, prototyping, and evaluation. After identifying key features through literature review and surveys, a low-fidelity prototype was created during the designing alternatives phase. Numerous revisions were made to the prototype following user testing. The second prototype was well received, leading to the development of the high-fidelity prototype. The correct use of terminology and clear navigation design were deemed critical for the usability of the GIGEASE application. The project is expected to make a valuable contribution to IIUM and the local Gombak communities, with the potential to significantly improve community wellbeing.